Taṭwīru Wasīlah al-Kahūt (Kahoot) fī Ta’līm Mahārah al-Qirā’ah li Țullāb al-Madrasah al-‘Āliyah - Ngaisah, Siti; Putra, Wahyu Hanafi; Setyowati, Nanik (Study Program of Arabic Language Teaching, 2025)
The objectives of this research are: 1) To determine the development of the Kahoot method in teaching reading skills at MA Nahdlatul Ummah. 2) Knowing the effectiveness of developing the Kahoot method in learning reading skills at MA Nahdlatul Ummah. The methodology used in this university research is research and development based on the Borg & Gall model. The data in this study are the characteristics of students, activities, and daily activities of students during learning, which are sourced from information from Arabic language teachers and data available on learning devices. The population is all twelfth-grade students of MA Ma'arif Nahdlatul Ummah using a purposive sampling technique with 23 students as the research sample. Interviews, observations, questionnaires, and tests carry out data collection techniques. The data analysis techniques used are qualitative and quantitative. This study highlights the effectiveness of the Kahoot approach to improve reading skills. The process involves several steps: identifying issues through interviews, gathering data via questionnaires to understand development needs, designing the production, which includes downloading Kahoot and creating content for reading skills, certifying the production with input from experts, enhancing the product based on recommendations, and applying it in a practical setting. The trial was conducted at MA Nahdlatul Ummah with pre-test and post-test evaluations. The results showed significant improvements in students' reading skills, indicating that Kahoot effectively aids in learning.